2020
DOI: 10.1177/1096348020963699
|View full text |Cite
|
Sign up to set email alerts
|

Silence is not Golden: Motivating Employee Voice through Inclusive Leadership

Abstract: Given the dynamic nature of the hospitality industry, firms must continuously improve to remain viable. Many innovations and improvements in service are driven by the experiences of employees on the front lines of service delivery, who have direct knowledge of what works and what does not in the day-to-day operation of a hospitality business. Unfortunately, research indicates that employees are not likely to speak up with opinions, ideas, and suggestions, behavior known as employee voice, unless they have some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 63 publications
1
34
0
2
Order By: Relevance
“…The findings can be interpreted in line with the small amount of existing literature on the topic; specifically, a work climate that is supportive of and validating one's true self (as an inclusive climate is) would elicit an organization's ability to satisfy its employees' basic psychological needs [39]. In turn, the employees' enhanced feeling of fulfilment in independently initiating action at work (autonomy), effectively mastering work activities and being confident about possessing the required skills (competence), as well as being part of an in-group based on meaningful relationships (relatedness), would lead them to engage in proactive discretionary behaviors aimed at challenging the work processes with the intention to improve them [107].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings can be interpreted in line with the small amount of existing literature on the topic; specifically, a work climate that is supportive of and validating one's true self (as an inclusive climate is) would elicit an organization's ability to satisfy its employees' basic psychological needs [39]. In turn, the employees' enhanced feeling of fulfilment in independently initiating action at work (autonomy), effectively mastering work activities and being confident about possessing the required skills (competence), as well as being part of an in-group based on meaningful relationships (relatedness), would lead them to engage in proactive discretionary behaviors aimed at challenging the work processes with the intention to improve them [107].…”
Section: Discussionmentioning
confidence: 99%
“…They have found that an inclusive leadership behavior, one that nurtures a sense of openness, availability, and belongingness, leads to the satisfaction of followers' needs [105,106], and that this fulfilment has a central role between inclusion and voice. This is because, in order to engage in voice behavior, one should believe his/her action and inputs will be effective (competence), and they should feel safe enough about their group membership to speak up (relatedness) [107]. Moreover, the sense of independence in freely choosing to initiate an action at work (autonomy) would elicit a motivation to engage in more conscientious behaviors that help preserve and support the growth and advancement of the organization [68].…”
Section: The Relationship Between Inclusion Psychological Needs Satisfaction and Voicementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the above research findings, studies on inclusive leadership are still in the early stage and more research attention is needed (e.g., Choi et al, 2017;Tran and Choi, 2019;Jolly and Lee, 2021;Wang and Shi, 2021). The current literature is mainly restricted to the influence of inclusive leadership in the work domain, leaving consequences in the family domain ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Inclusive leadership, defined as “leaders who exhibit openness, accessibility, and availability in their interactions with followers” ( Carmeli et al, 2010 , p. 250), has drawn increasing attention in recent years. Researchers have found that inclusive leadership is positively related to subordinates’ affective organizational commitment and work engagement ( Choi et al, 2015 ), psychological safety ( Hirak et al, 2012 ; Javed et al, 2017 ; Wang and Shi, 2021 ), well-being ( Choi et al, 2017 ), creativity ( Carmeli et al, 2010 ; Javed et al, 2017 , 2018 ), organizational citizenship behavior ( Tran and Choi, 2019 ), and voicing behaviors ( Yin, 2013 ; Jolly and Lee, 2021 ).…”
Section: Introductionmentioning
confidence: 99%